Pengaruh Kepemimpinan Transformasional Terhadap Kekompakan, Keterlibatan Kerja Dan Kinerja Pegawai (Studi Penyusunan Dokumen Perencanaan Pembangunan Satuan Kerja Perangkat Daerah Kabupaten Kotabaru) - Muhamad Ansar Nur (Universitas Lambung Mangkurat, 2017)
The increasing of employees’ job performance on public (government) organization is an important and strategic substance against the development dynamic which from time to time is faced with increasingly complex global challenges. The purpose of this study is to test and analyze of the influence transformational on cohesiveness, job involvement and employees’ job performance. The study is designed to answer any formulaic problems, while also testing any given hypothesis at the same time.The study is a quantitative research which will prove causal relationship between latent exogenous variable (independent variable) of transformational leadership (X) with latent endogen dependent variable to job performance (Y3) and latent endogen intervening variable cohesiveness (Y1) and job involvement (Y2). Target populations in this study are structural officials (echelon II, III, and IV) in total of 560 people with samples amount to 150 people. Sample acquiring technique uses stratified proportional random sampling and data analysis using Structural Equation Modeling (SEM) with AMOS (Analysis of Moment Structure) program version 18.The result of the study shows that the transformational leadership have positive and significant influence on employees’ job performance. The result of the study also shows transformational leadership have positive and significant influence on cohesiveness and job involvement. As are cohesiveness and job involvement have positive and significant influence on employees’ job performance. Key Words : Transformational Leadership, Cohesiveness, Job Involvement and Job Performance.